Towards developing e-rental houses for UiTM community / Johanna Ahmad - Ahmad, Johanna (2006)
Rental Houses System has been widely implemented all over the world. Tenants by the thousands began visiting the websites looking for homes for rent and viewing the rental houses. Rental Houses System is a good, economical way to bring in great, high quality leads. Currently the "Unit Kebajikan NR" only provided manual services for the student to view list of rental houses information. This project was developed as a solution for those problems occurs using the manual processes. The objective of this research is to identify the user requirements for E-Rental Houses. The requirements were gained from interviewing the staffs of "Unit Kebajikan NR" and some of house owners. Questionnaires also distributed to students, house owners and staffs that will interact with the new system. Web observations also done to find a tabulate of functionality template for E-Rental Houses system. Based on the requirements,the researcher design a prototype system of E-Rental Houses using PHP and MySQL. E-Rental Houses allows students to search list of rental houses and booking rental house via short message service (SMS). Through the approach and findings in this research, the researcher manages to achieve all of the objectives of my research mentioned above